A framework for investigating space-borne polarimetric interferometry using the ALOS-PALSAR sensor - Cloude, Shane; Krieger, Gerhard; Papathanassiou, Konstantinos (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2005)
In this paper we present an analysis of the potential for implementing polarimetric SAR Interferometry (POLInSAR) with the new L band phased array SAR sensor (PALSAR) to be launched on board the JAXA-ALOS satellite. We first summarise a new system design concept, the phase tube, we have developed for general POLInSAR assessment and then present a detailed analysis of the dual and quadpol modes of ALOS-PALSAR. © 2005 IEEE.
DLR Import::2019-04-03